Ideology, caste, class, and gender - Thiruchandran, Selvy (New Delhi : Vikas Pub. House : Distributors, UBS Publishers' Distributors, 1997)
Study with special references to Tamil Nadu, India.
Keywords: Women -- India -- Tamil Nadu; Tamil Nadu (India) -- Social conditions; Tamil Nadu (India) -- Economic conditions